2012
DOI: 10.1063/1.4759448
|View full text |Cite
|
Sign up to set email alerts
|

1,1-diamino-2,2-dinitroethylene under high pressure-temperature

Abstract: The structural phase stability of 1,1-diamino-2,2-dinitroethylene (FOX-7) has been studied up to 10 GPa through isothermal compression at 100 °C and 200 °C using synchrotron mid- and far-infrared spectroscopy. During isothermal compression at 100 °C changes are observed in vibrational spectra with increase in pressure that are indicative of significant distortion to monoclinic α phase or a possible structural transformation to a high pressure α(') phase at 2.2 GPa and α(") phase at 6.1 GPa. At 200 °C, for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 28 publications
1
49
2
Order By: Relevance
“…Due to these attractive characteristics, many studies have been performed on its synthesis, 1,2 polymorphism, [3][4][5][6][7] thermal analysis, [8][9][10][11] and crystallization. Due to these attractive characteristics, many studies have been performed on its synthesis, 1,2 polymorphism, [3][4][5][6][7] thermal analysis, [8][9][10][11] and crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these attractive characteristics, many studies have been performed on its synthesis, 1,2 polymorphism, [3][4][5][6][7] thermal analysis, [8][9][10][11] and crystallization. Due to these attractive characteristics, many studies have been performed on its synthesis, 1,2 polymorphism, [3][4][5][6][7] thermal analysis, [8][9][10][11] and crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…However, they found that no lattice transformations could be observed up to 8 GPa under hydrostatic conditions. Recent experiments at different temperatures and pressures found three possible phase transitions (at 2 GPa, 5 GPa and above 10 GPa) in mid and far IR regions 11,12 . Pravica et al 11 reported the strengthening of the hydrogen bond and softening of NH 2 stretching frequencies at high pressure by using IR experiments.…”
mentioning
confidence: 99%
“…Starting from the synthesis of this compound in 1998 3 , several studies were carried out to investigate its structural properties from ambient 4 to extreme conditions [5][6][7][8] , its thermal behavior with decomposition mechanism 9,10 and vibrational spectroscopy (IR and Raman) at different pressures and temperatures 5,11,12 . Beeman and Ostrak 4 determined the crystal structure of FOX-7 to be monoclinic with the space group P2 1 /n, which contains four molecules (56 atoms) per unit cell.…”
mentioning
confidence: 99%
“…Recent data indicate possiblee xistence of the fourth modification of this compound, d-FOX-7, which is stable above 453 Ku ntil the compound decomposes above 524 K [5,8,[11][12][13].I nt he cited papers, the conclusion on the existence of d-FOX-7 wasm ade based on IR spectroscopic data and on the enhancement of thermals tability of FOX-7 after heating at temperatures above 488 K. The heat effect of the g!d transformation was not reported since this process proceeds after the onset of thermal decomposition of FOX-7.…”
Section: Introductionmentioning
confidence: 99%
“…At normal pressure the a-phase is stable below 373 K [ 1] and the stability range of the b-phase is 373-418 K [ 1,2]. The g-phase has been considered to exist from 435 Ku ntil rapid thermal decomposition at 504 K[ 2],b ut lateri tw as shown [1,3,4] that at ambient pressure the boundary between the areas of thermodynamics tability of b-a nd g-FOX-7 lies in the range of 418-423 K.High-temperature conversions of FOX-7, includingi ts thermal decomposition, have been investigated intensely [5][6][7][8][9][10].Recent data indicate possiblee xistence of the fourth modification of this compound, d-FOX-7, which is stable above 453 Ku ntil the compound decomposes above 524 K [5,8,[11][12][13].I nt he cited papers, the conclusion on the existence of d-FOX-7 wasm ade based on IR spectroscopic data and on the enhancement of thermals tability of FOX-7 after heating at temperatures above 488 K. The heat effect of the g!d transformation was not reported since this process proceeds after the onset of thermal decomposition of FOX-7.According to Refs. [8,9],d ecompositiono fF OX-7 in the temperature range 463-488Kis accompanied bym ass loss of 30-40 %a nd polymorphous transition of g-phase into hypothetical d-polymorph.The pressure-temperature (P-T)p hase diagram of FOX-7 was determined basedo nt he data obtained by means of in situ synchrotron infrared radiations pectroscopya nd available literature values [11].A ccording to this diagram, at room temperature a-FOX-7 transforms in high-pressure modifications Ia nd II above 2and 4.5 GPa, respectively.The phased iagrams uggests the existence of two potential triple points at high P and T values: b + g + d and a + b + d.[a] V.Abstract:S tucturalt ransformations of 1,1-diamino-2,2-dinitroethene( FOX-7) were investigated in the temperature range 298-513 Kbymeans of DSC,TG, isothermal calorimetry,P XRD, IR spectroscopy, and electron microscopy.T he data obtained confirmt he existenceo ft he high-temperature d-FOX-7 polymorph stable above 480 K. The heat effect of the g!d transformation is À 4.6 Jg À1 (À680 Jmol À1 ).…”
mentioning
confidence: 99%